Resilience trade-offs: addressing multiple scales and temporal aspects of urban resilience. (April 2015) - Chelleri, Lorenzo; Waters, James J; Olazabal, Marta; Minucci, Guido
The concept of urban resilience has so far been related mainly to climate change adaptation and disaster management perspectives. Here we aim to broaden the discussion by showing how the framework of urban resilience should be related to wider sustainability challenges, including i) climate change and natural hazard threats, ii) unsustainable urban metabolism patterns and iii) increasing social inequalities in cities. Using three case studies (flood risk management in the Dutch polders, urban–rural teleconnections driving the Bolivian quinoa market, and spatial diversity in the adaptive capacity of Kampala slums), (1) we draw out significant insights related to scales and sustainability, which will push urban resilience research forward. The key "move" is to consider both spatial and temporal interactions, in order to shift from the mainstreaming of the resilience-building paradigm toward a critical understanding and management of resilience trade-offs. While urban resilience emerges not necessarily as a normatively positive concept anymore, we argue that addressing multi-scale and temporal aspects of urban resilience will allow greater understanding of global sustainability challenges.